Personality, Lifestyle, and Values as Predictors of Behavioral Intention towards Generative AI among Generation Z - Christiano, Bryan; Wijaya, Jasen; Sanjaya, Budianto; Tantowi, Sebastian (APPS Publications, 2024)
The aim of the study is to explore and understand the multifaceted and reciprocal relationship between users (specifically highlighting Generation Z) and the rapidly growing field of Generative AI, including its impact on both users and the technology’s development, while also emphasizing the importance of ethical considerations and the need for a balanced approach grounded in psychometric theory. This quantitative study investigates the influence of personality, lifestyle, and values (independent variables) on the behavioral intention to adopt generative AI products (dependent variable) among Generation Z individuals aged 17-25 in the JABODETABEK area of Indonesia, utilizing online questionnaires with Likert and nominal scales, and analyzing the collected data through multiple linear regression and PLS-SEM. The methodology involves purposive random sampling to target Gen Z users of generative AI within the specified demographic and geographic criteria for data collection and subsequent statistical analysis to test the hypothesized relationships between the variables. Consumer personality, consumer lifestyle, and consumer values all have a positive and significant effect on the behavioral intention to use generative AI-based products. This indicates that individuals with certain personality traits, lifestyles, and value systems are more inclined to adopt and use these AI tools. The majority of respondents were aged 20-22 and resided in the JABODETABEK area, with a very high percentage (93.8%) reporting usage of generative AI products and an even higher percentage (94.5%) specifically using ChatGPT. The specific combination of examining the complex, reciprocal relationship between Gen Z and Generative AI, coupled with the emphasis on ethical implications, appears to be the novel contribution highlighted in this introduction.